The moderating effect of government ownership on the relationship between corporate governance mechanisms and voluntary disclosure in Saudi Arabia and United Arab Emirates / Yaseen Al-Janadi - Al-Janadi, Yaseen (2010)
The main objective of this dissertation is to show the impact of internal and external corporate governance mechanisms on voluntary disclosure. Corporate governance plays an important role as a monitoring system and consequently provides quality reporting not only for shareholders but for stakeholders as well. Additionally, the study aims to examine the moderating impact of government ownership on the association of corporate governance mechanisms with voluntary disclosure. The study also aims to measure the level and quality of voluntary disclosure in Saudi Arabia and the United Arab Emirates (UAE). In this thesis, voluntary disclosure is measured by developing a score that consists of three levels of measurement. The sample consists of 150 listed companies, 87 companies from the Saudi Stock Market and 63 companies from the two UAE Stock Markets which are the Abu Dhabi Securities Exchange (ADX) with 31 companies and the Dubai Financial Market (DFM) with 32 companies. The data is collected from the annual reports for the available financial years 2006 and 2007. The study uses univariate and multivariate analysis to examine the association of corporate governance mechanisms with voluntary disclosure